Making smallholder value chain partnerships inclusive: exploring digital farm monitoring through farmer friendly smartphone platforms - Agyekumhene, Christopher; Vries, J. de; Paassen, A. van; Schut, Marc; MacNaghten, P. (MDPI, 2020)
Value chain partnerships face difficulties achieving inclusive relations, often leading to unsustainable collaboration. Improving information flow between actors has been argued to contribute positively to a sense of inclusion in such partnership arrangements. Smallholders however usually lack the capability to use advanced communication technologies such as smartphones which offer a means for elaborate forms of information exchange. This study explores to what extent co-designing smartphone platforms with smallholders for farm monitoring contributes to smallholder ability to communicate, and how this influences smallholder sense of inclusion. The study uses an Action Design Research approach in engaging smallholders in Ghana, through multi-stakeholder and focus group discussions, in a reflexive co-design process. The research finds that co-designing a platform interface was significant in improving farmer ability to comprehend and use smartphone based platforms for communicating farm conditions and their needs with value chain partners. Farmers were however skeptical of making demands based on the platform due to their lack of power and mistrust of other actors. This highlights a need for adjusting the social and political dimensions of partnership interactions, in tandem with the advancement of digital tools, in order to effectively facilitate a sense of inclusiveness in partnerships.